Symptom scores in the diagnosis of pediatric cow's milk protein allergy: A systematic review. Issue 7 (28th May 2021) - Thompson, Georgina; Zhelev, Zhivko; Peters, Jaime; Khalid, Sara; Briscoe, Simon; Shaw, Liz; Nunns, Michael; Ludman, Sian; Hyde, Christopher
Abstract: Background: Cow's milk protein allergy (CMPA) is an immune‐mediated allergic response to proteins in milk that is common in infants. Broad CMPA symptoms make diagnosis a challenge, particularly in primary care. Symptom scores may improve a clinician's awareness of symptoms, indicating a need for further testing. This systematic review examined the development and evaluation of such symptom scores for use in infants. Methods: CENTRAL, MEDLINE, EMBASE and CINAHL databases were searched from inception to 3 December 2019 (Updated 14 November 2020) for diagnostic accuracy studies, randomised controlled trials, observational studies, economic evaluations, qualitative studies and studies reporting development of the tools. Data were not suitable for meta‐analysis due to clinical and methodological heterogeneity, so were narratively synthesised. Results: We found two symptom scores evaluated in one and fourteen studies, respectively. Estimated sensitivity and specificity ranged from 37% to 98% and 38% to 93%. The evaluations of each tool were at high risk of bias or failed to address issues such as clinical and cost‐effectiveness. Conclusions: Estimates of accuracy of symptom scores for CMPA offered so far should be interpreted cautiously. Rigorous, conflict‐free research based on well‐defined roles for the tools is urgently required. Abstract :